PERSON MARKERS IN NON-NATIVE STUDENTS’ WRITING - Bikelienė, Lina (Verbum, 2016)
The present paper seeks to analyse person markers, which refer to “the use of first person pronouns and possessive adjectives” (Hyland 2014(1999), p. 104), in university learner English. Students are constantly encouraged to aim at academic register, one of the features of which is an attempt at objectivity. While this could be achieved by using an impersonal style, “writers gain credibility by projecting an identity invested with individual authority, displaying confidence in their evaluations and commitment to their ideas” (Hyland 2002, p. 1091). Writers, therefore, have to find the right level of balance between invisibility and visibility in their work. Person markers, as one of the most important linguistic means to create authorial presence (Burneikaitė 2013), being subjected to genre constraints, pose numerous problems to non-native students who have repeatedly been characterised as lacking in awareness of genre conventions and having problems with formal register (Breeze 2007). Though the topic of authorial stance has been researched widely, there has been little analysis of Lithuanian learners’ English data (cf. Burneikaitė 2008, 2013). In addition, no research has been found that analysed genre or institution variables in the use of person markers in Lithuanian undergraduates’ writing. This shows a need for the present study, which focuses on genre, language proficiency, institutional, and L1 variables. The data for the study was retrieved from a number of corpora representing non-native (Lithuanian) and native (English) university students’ language. The results indicate different roles of the variables in the explicit expression of authorial stance by person markers.
Keywords: learner corpora; writer visibility; person markers